PARAMETRIC MODELING AND AI IN MODERN SCULPTURE EDUCATION - Bhosale, J. P.; Korwar, Dipti Ganesh; Goyal, Shweta; Neha; Singh, Manoj Kumar; Shyam, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The use of parametric modeling and artificial intelligence (AI) is quickly transforming the current education of sculpture by bringing in computational practices that create expansions of formal inquiry, material cognition, and design practice that reflects. In this paper, the authors explore how parametric modeling and AI-driven approaches can be taken into consideration in the field of contemporary sculpture lessons and to place these technologies as the complementary, but not substitutive, tools of human artistic authority. The paper follows the history of computer-assisted sculptural work, analyzes the most important parametric and AI algorithms to create forms and suggests a hybridized parametric-AI design pipeline, which can be applied to the studio learning setting. Structured evaluation metrics, where creativity, formal complexity, and technical performance are related, are used to analyze experimental sculptural prototypes, with the help of visual analytics. The paper addresses pedagogical issues, authorship, and the technological restrictions that are connected with AI-aided sculpture education. Placing parametric modeling and AI into a cognitive and creative collaboration in the sculptural practice, this work adds a systematic instructive approach in training future sculptors to work in digitally enhanced and interdisciplinary creative contexts.